Tension and Paradox in Women-Oriented Sustainable Hybrid Organizations: A Duality of Ethics - Palakshappa N; Dodds S; Grant S (Springer)
The pursuit of social goals and ethics in business creates challenges. Sustained efforts to address poverty, environmental degradation or health/wellbeing require meaningful and transformative responses that impact across multiple levels—individual, community and the global collective. Shifting predominant paradigms to facilitate change entails a renegotiation of business strategy—between organizations, their purpose(s), individual and collective stakeholders and ultimately with society at large. Hybrid organizations such as social enterprises are positioned to affect such change. However, in balancing divergent goals such organizations encounter tensions and paradox, creating a duality of ethics. Utilizing in-depth interviews to develop a case within the sustainable fashion industry, we identify tensions and paradox within women-oriented hybrid organizations. Significantly, managing these tensions and paradox results in multiple dualities of ethics, often with a wider impact on organizational founders/managers. We find three interrelated ethical dualities: business strategy and personal values; financial sustainability and holistic sustainability; and business, employee, societal wellbeing, and personal wellbeing. This insight is noteworthy when looked at within the broader context of sustainability and highlights the importance of sustainability in women-oriented hybrid organizations.
Keywords: 1503 Business and Management; 1505 Marketing; 2201 Applied Ethics